2023
DOI: 10.3389/ti.2023.11819
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Experience Among Liver and Kidney Transplant Recipients: A Mixed Methods Study

Dami Ko,
Julia Dierker,
Rebecca Stouff
et al.

Abstract: Telehealth has become widely available to solid organ transplant (SOT) recipients during the COVID-19 pandemic. While evidence suggests that telehealth serves as an acceptable alternative for most SOT recipients, their satisfaction and its context remain unclear. This study used a mixed methods approach to investigate the perspectives of SOT recipients (i.e., liver, kidney, and simultaneous liver-kidney) on the benefits and disadvantages of telehealth. A total of 252 adult SOT recipients completed an online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…PROs can also guide PCC by identifying models of care acceptable to patients. To this end, several studies have shown the acceptability of telemedicine for outpatient hepatology care 29–31 …”
Section: Clinical Application Of Pros Within Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…PROs can also guide PCC by identifying models of care acceptable to patients. To this end, several studies have shown the acceptability of telemedicine for outpatient hepatology care 29–31 …”
Section: Clinical Application Of Pros Within Liver Diseasesmentioning
confidence: 99%
“…To this end, several studies have shown the acceptability of telemedicine for outpatient hepatology care. [29][30][31] PROs are categorized into generic and diseasespecific instruments. Generic instruments such as Patient-Reported Outcome Measurement Information System Profile 29 (PROMIS-29) (assessing 7 health domains-physical function, fatigue, social function, depression, anxiety, pain interference and social function, and pain intensity), Edmonton Symptom Assessment System (assessing symptom burden), Patient Health Questionnaire-9 (assessing depression) can be used clinically.…”
Section: Clinical Application Of Pros Within Liver Diseasesmentioning
confidence: 99%